ANALISIS KELAYAKAN ASPEK KEUANGAN RENCANA PENGEMBANGAN USAHA PEMBUATAN BRIKET SEKAM PADI (Studi Kasus Pada UMKM Desa Waringinkarya Kab Karawang) - Hendri Nur Ardiansyah (Politeknik Bisnis Indonesia, 2023)
The financial feasibility analysis is a part of a business assessment using theories in financial management. Briquette products are solid fuels made from biomass materials with high economic value. Waringinkarya is a village with the potential for biomass resources derived from rice waste that can be utilized as raw materials for briquette production. This research aims to determine the feasibility aspects of briquette manufacturing with the object being the UMKM involved in charcoal production in Waringinkarya Village. The research method used is a descriptive-analytical method, employing business feasibility analysis criteria such as PP, ARR, NPV, IRR, and PI. The research results indicate that the briquette production plan has a PP period of 3.42 months, ARR of 703%, NPV of Rp 3,224,997,657, IRR of 351%, and PI of 14.80. Based on the research findings, it can be concluded that the business plan for briquette production using rice husk waste as raw material is feasible for implementation based on financial aspects.